Search for B+→ℓ+νℓ recoiling against B−→D0ℓ−ν[bar]X - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a search for the decay B+→ℓ+νℓ(ℓ=τ,μ, or e) in (458.9±5.1)×106 BB[bar] pairs recorded with the BABAR detector at the PEP-II B-factory. We search for these B decays in a sample of B+B− events where one B-meson is reconstructed as B−→D0ℓ−¯νX. Using the method of Feldman and Cousins, we obtain B(B+→τ+ντ)=(1.7±0.8±0.2)×10−4, which excludes zero at 2.3σ. We interpret the central value in the context of the standard model and find the B meson decay constant to be f2B=(62±31)×103 MeV2. We find no evidence for B+→e+νe and B+→μ+νμ and set upper limits at the 90% C.L. B(B+→e+νe)<0.8×10−5 and B(B+→μ+νμ)<1.1×10−5.